2012
DOI: 10.1111/j.1538-7836.2012.04875.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between post‐treatment platelet reactivity and ischemic and bleeding events at 1‐year follow‐up in patients receiving prasugrel

Abstract: confidence interval [CI]: 1.2-1.72; P < 0.001 and OR: 0.75, 95% CI: 0.59-0.96; P = 0.024 [respectively, per 10% increase]). Conclusion: Platelet reactivity measurement after a prasugrel LD predicts both ischemic and bleeding events at 1 year follow-up for ACS patients undergoing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 26 publications
11
74
0
6
Order By: Relevance
“…With regard to the evaluation of platelet reactivity responses to P2Y12 inhibitors, platelet function monitoring can not only predict ischemia but also bleeding events. 17 In our 30-day Our current study produced results in line with previous head-to-head comparison studies of prasugrel and ticagrelor in STEMI patients. 4,7 Previous studies have focused on platelet inhibition in the very early phase, whereas we focused on the 48-h period as a bridging time point between acute and chronic antiplatelet therapy.…”
Section: Population and Clinical Baseline Characteristicssupporting
confidence: 86%
“…With regard to the evaluation of platelet reactivity responses to P2Y12 inhibitors, platelet function monitoring can not only predict ischemia but also bleeding events. 17 In our 30-day Our current study produced results in line with previous head-to-head comparison studies of prasugrel and ticagrelor in STEMI patients. 4,7 Previous studies have focused on platelet inhibition in the very early phase, whereas we focused on the 48-h period as a bridging time point between acute and chronic antiplatelet therapy.…”
Section: Population and Clinical Baseline Characteristicssupporting
confidence: 86%
“…6,9 It is widely accepted that HPR is associated with adverse events, whereas some studies have also suggested a possible link between LPR and bleeding. [24][25][26][27] During the 30 days of follow-up in this study, no major bleeding event occurred in either treatment arm. Eight patients (5 allocated to the ticagrelor arm and 3 to the clopidogrel arm) experienced BARC1 or BARC2 bleeding complications.…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy and safety results of TRITON-TIMI 38 and the PRASFIT studies should be discussed in the context of the therapeutic window of antiplatelet activity. This concept implies that the risk of thrombotic events is increased in patients with high on-treatment platelet reactivity (i.e., low platelet inhibition), and that the risk of bleeding is increased in patients with low on-treatment platelet reactivity (i.e., high platelet inhibition) [26][27][28][29].…”
Section: Risk Of Bleeding In the Prasfit Studiesmentioning
confidence: 99%